2022
DOI: 10.3390/en15134557
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Framework for Assessment of Mergers and Acquisitions in Energy Sector

Abstract: According to Thomson Reuters DataStream database, 22,458 merger and acquisition (M&A) transactions with a deal value exceeding 7016 billion Euros have occurred in the energy worldwide sector during 1995–2020. International M&A enable promotion of sustainable competitive advantages, accelerates industry developments and helps to promote sustainable social and economic development. Our research aims to systemize empirical studies, which would enable assessment of the relationship between M&A transact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Second, they face serious competition from new entrants due to the transition of the industry from traditional to new business models. To establish new utility business models, they have been acquiring new technologies in green business, energy storage, AI, smart energy, smart operations, platform operations, and big data processing, e.g., as discussed in [1,[25][26][27][28][29][30][31], through innovation and competitive strategies. Such strategies often appear in companies' R&D expenses and patent applications.…”
Section: The Literature On the Mandas Of Electric Power Utilitiesmentioning
confidence: 99%
“…Second, they face serious competition from new entrants due to the transition of the industry from traditional to new business models. To establish new utility business models, they have been acquiring new technologies in green business, energy storage, AI, smart energy, smart operations, platform operations, and big data processing, e.g., as discussed in [1,[25][26][27][28][29][30][31], through innovation and competitive strategies. Such strategies often appear in companies' R&D expenses and patent applications.…”
Section: The Literature On the Mandas Of Electric Power Utilitiesmentioning
confidence: 99%
“…Mergers and acquisitions differ significantly even though they represent a particular corporate economic investment form. Mergers typically involve multiple entities combining their operations and consolidating resources under a single entity, whereas acquisitions refer to a specific company exercising control over the assets of another company [5].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Through the coordination and alignment of operational functions, organizations can optimize resource allocation, reduce waste, and improve productivity. Andriuškevičius and Štreimikienė (2022) found that operational synergy enhances resource utilization, thereby positively impacting firm performance outcomes such as throughput and cycle time reduction. Operational synergy also plays a crucial role in driving quality improvement and fostering innovation.…”
Section: Introductionmentioning
confidence: 99%